Standardization of Visible Kinetic Assay for the Estimation of Plasma Glucose by Glucose Oxidase and Peroxidase Method - Bhatt, M.P.; Rai, N.; Pokhrel, S.; Acharya, P.; Marhatta, S.B.; Khanal, D.P.; Nagila, A.; Chataut, P.D. (Journal of Manmohan Memorial Institute of Health Sciences, 2021)
Objective: In the clinical laboratory, glucose is the most frequently analyzed test in blood which plays a vital role in the diagnosis and management of patients suffering from diabetes mellitus and metabolic disorders. The glucose oxidase and peroxidase (GOD-POD) method is an end point reaction method for glucose estimation, which is cheap and readily available in routine laboratories with significant time consumption. However, Glucose estimation by hexokinase is available for rapid estimation that may cost comparatively higher for the routine laboratories. Thus, our study is designed to standardize rapid and convenient method of plasma glucose estimation with modification by kinetic mode based on GOD-POD reaction for the rapid and high through put analysis of glucose estimation using semi-automated or autoanalyzers. Method: Photometric linearity of the kinetic method is compared with that of end point reaction methods. Furthermore, correlation between an endpoint and kinetic method was determined using Pearson correlation using plasma from normal and diabetic patients (n=32) visiting Manmohan Memorial Teaching Hospital, Kathmandu. Result: Our study showed, significant positive correlation between the end point and the kinetic method (r=0.99) The linearity of modified kinetic (GOD-POD) method is up to 400 mg/dl in comparison to that of existing end point method (500 mg/dl), which covers the normoglycemic to pathological hyperglycemic range of glucose estimation in routine laboratories. Conclusion: The significant positive correlation of our visible kinetic method with end point reaction method shows possibilities for the high through put and rapid analysis of the glucose estimation in 3 minute using semi-automated and autoanalizers.